The Effect of Chamfering Structure towards the Design of Open Loop Resonator Bandpass Filter for Microwave Applications - Noor, N.N.M.; Mat, D.A.A.; Amira, A.; Zaidel, D.N.A.; Joseph, A. (UTEM, 2017)
Filter is the most essential components in the transceiver system. It is used to accept and reject any unwanted frequencies that falls out of the bands. Recently, the design of bandpass filter (BPF) has been a great challenges for RF designer. Although many researches have designed filter in the unlicensed frequency but most of the filter suffered from high insertion loss, inadequate selectivity and wider bandwidth. Therefore, this project design an Open-Loop Resonator Bandpass Filter (OLRBPF) to produce a low loss filter to operate at 2.4 GHz frequency. In order to overcome the high insertion loss, chamfered bend is introduced and implemented at the OLRBPF’s structure. This will reduce the radiation loss produced and enhanced the coupling between both resonators of the filter. The results show that the proposed OLRBPF produce better insertion loss compare to conventional filter.